1995
DOI: 10.1212/wnl.45.10.1923
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose, short-term oral prednisone in the treatment of carpal tunnel syndrome

Abstract: We evaluated the effectiveness of low-dose, short-term oral prednisone in ameliorating the pain and other symptoms of carpal tunnel syndrome (CTS) in a randomized, double-blind, placebo-controlled study of patients with mild to moderate CTS. Prednisone, in doses of 20 mg daily for the first week and 10 mg daily for the second week, resulted in significant improvement in global symptom scores. The effect was rapid, but gradually waned over 8 weeks of observation. This approach may provide a treatment alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 2 publications
1
44
0
5
Order By: Relevance
“…3 NO. 13 oral steroids [101][102][103] and therapeutic ultrasound, 104,105 and limited evidence (findings from one RCT) for the effectiveness of yoga 106 and carpal bone mobilisation. 107 Evidence from a second Cochrane systematic review 108 indicated that local corticosteroid injections provided greater improvement in clinical symptoms after 1 month than placebo injections.…”
Section: Overview Of Evidence On Non-surgical Interventionsmentioning
confidence: 99%
“…3 NO. 13 oral steroids [101][102][103] and therapeutic ultrasound, 104,105 and limited evidence (findings from one RCT) for the effectiveness of yoga 106 and carpal bone mobilisation. 107 Evidence from a second Cochrane systematic review 108 indicated that local corticosteroid injections provided greater improvement in clinical symptoms after 1 month than placebo injections.…”
Section: Overview Of Evidence On Non-surgical Interventionsmentioning
confidence: 99%
“…The longterm differences between the groups could not be evaluated, because only patients who improved after 4 weeks were assessed after 6 months. The low quality study [25] evaluated the effect of an oral steroid.After 2 weeks there was significantly more improvement in symptoms in the steroid group, compared with the placebo group, but this effect had disappeared after 4 and 8 weeks.…”
Section: Other Types Of Oral Medicationsmentioning
confidence: 99%
“…16,18 Of the RCTs on surgical techniques 7 RCTs compared endoscopic carpal tunnel release with open carpal tunnel release (OCTR), 19 -26 3 RCTs evaluated the effect of OCTR with a new incision technique versus OCTR with a standard incision, 27-30 and 3 RCTs compared OCTR with additional internal neurolysis with OCTR alone. [31][32][33][34] Data presentation in the RCTs concerning conservative treatment options for CTS was generally adequate.…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used outcome measures were those related to symptoms of CTS. A wide variety of those measures were used including the following: specific descriptions of symptoms (eg, pain, paraesthesias), 11,13 more general expressions (eg, night discomfort or just symptoms), 10,14 combinations of symptoms (eg, night/day pain/paraesthesias, global symptom score), 13,16,18 measures relating to improvement of symptoms (eg, symptoms improved/changed/worsened), 15 or severity of symptoms (eg, main complaints: no complaints at all [0] to the most intense complaints I can imagine [10]). 12 Because pooling of heterogeneous outcomes will lead to an uninterpretable and misleading pooled estimate, meta-analysis is not feasible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation